High-temperature tribological properties of NiCoCrAlY-WSe2-BaF2·CaF2 solid lubricant coatings prepared by plasma spraying. Issue 1 (November 2015) - Chen, X H; Yuan, X J; Xia, J; Yu, Z H
Abstract: In this paper, NiCoCrAlY-WSe2 -BaF2 ·CaF2 solid lubricant coatings were produced on a substrate by plasma spray and investigated at the high temperature, such as 500 °C and 800 °C. The structure of the coatings was characterized using XRD pattern and scanning electron microscopy. The TC1 (83wt% NiCoCrAlY) coating has a low friction coefficient at 500C, where the WSe2 is a good solid lubricant. The TC2 (65wt% NiCoCrAlY) coating has the low friction coefficient (0.279) at 800°C, due to the formation of BaCrO4 on the surfaces. As a result, the TC2 coating has the optimal tribological property in the wide temperature.